Optimization of PV powered SPD switchable glazing to minimise probability of loss of power supply. (February 2019) - Ghosh, Aritra; Norton, Brian
Abstract: Suspended particle device (SPD) glazing is an electrically actuated switchable glazing. It requires alternate current (AC) power supply to switch from opaque to transparent state. To power this glazing using PV device requires inverter. Optimization of AC powered switchable SPD glazing using photovoltaic (PV) device has been evaluated using loss of power supply probability (LPSP). Electrically switchable direct current (DC) powered electrochromic glazing was also considered in this investigation as it doesn't need any inverter to couple with PV. It is concluded that behaviour of these glazings is the dominant factor in performance optimization outweighting than azimuthal orientation and inclination of PV. Highlights: PV powered SPD glazing was optimised using LPSP method. PV powered EC glazing was evaluated using LPSP method. Inverter requirement can be an obstacle for small scale PV powered SPD glazing.